MORPHOLOGICAL ANALYSIS OF WORD FORMATION PROCESS ON POLITICAL WORDS YOU TUBE PODCAST IN INDONESIA - Kulsum, Ummu (Pendidikan Agama Islam, 2022)
This journal article entitled “Morphological Analysis of Word Formation Process on political words YouTube podcast In Indonesia” aims to reveal the English word formation process and investigate the types of English process that appear, the change of basic meaning from the derived words occured, type of word formation process which is the most frequently used In YouTube podcast In Indonesia on 1st July 2023 edition. The analysis mainly uses a descriptive qualitative method or library method based on the theory of George Yule (2006) Fourth Edition and strenghtened by the theory of William o’ Grady (1984), Stefanny Jennady (1944) and Harimurti Kridalaksana ( 2007). In addition, oxford advanced learner’s dictionary 7th edition by wehmeimer,S,Ed, is also used to support the analysis. The data of the research is taken from the YouTube podcast about politic in Indonesia. Finding shows that researcher use the types of English word formation variously in the language used in the YouTube podcast. The English word formation process which are found are Acronym, abreviation, clipping, blending, borrowing, compounding, and derivation. It also shows that news writers try to make language that could be mentioned easily the English word Formation Process which Experience in the change of meaning are compounding and derivation and the most frequently use of English word formation Process is Derivation suffixes, suffixes and the prefixes. It seems from the finding result of the research that derivation hold the highest frequency in English word formation process in Politic Podcast.